The berimbau : soul of Brazilian music - Galm, Eric A. (University Press of Mississippi, 2010)
The Brazilian berimbau, a musical bow, is most commonly associated with the energetic martial art/dance/game of capoeira . This study explores the berimbau's stature from the 1950s to the present in diverse musical genres including bossa nova, samba-reggae, MPB (Popular Brazilian Music), electronic dance music, Brazilian art music, and more. Berimbau music spans oral and recorded historical traditions, connects Latin America to Africa, juxtaposes the sacred and profane, and unites nationally constructed notions of Brazilian identity across seemingly impenetrable barriers. The Berimbau: Soul o.